Clinical, Radiological Profile and Bronchoscopic Assessment of Non-Resolving Pneumonia Patients in a Tertiary Care Hospital - Rajendran, Saravanavasan; Navaneethakrishnan, Muthulakshmi; Alagappan, Kannan Muthuraman (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Community-Acquired Pneumonia (CAP) is one among many acute medical conditions that require hospitalisation. Majority of patients with CAP respond well to standard antimicrobial therapy while a minority (non-resolving pneumonia) fail to respond requiring further treatment. This study focuses on the clinical, radiological profile and bronchoscopic assessment of non-resolving pneumonia patients. The study also analyses the diagnostic yield of video bronchoscopy. Methods A cross-sectional study conducted among patients admitted with non-resolving pneumonia in a tertiary care centre in the time period from August 2015 to July 2018. A total 55 patients satisfying the inclusion criteria were enrolled in the study. Clinical history, radiological assessment and video bronchoscopy were done for all patients. The variables were presented as frequency tables using SPSS-17. Results Among the study participants, 44 patients were males while 11 were females. The majority belonged to the age group 51-60 years (38.2%). The most common clinical symptom and auscultatory finding were cough with expectoration (54%) and crackles (80%) respectively. The bronchoscopic finding was purulent secretions in majority (43.6%). BAL Cb-naat for Tuberculosis was positive in 41.8% and sensitive to rifampicin in all patients. Conclusions The study showed the need for early referral and evaluation of non-resolving pneumonia patients. Bronchoscopy was found to be a valid investigation modality with a good diagnostic yield.